Ibuprofen-Induced Hypokalemia and Distal Renal Tubular Acidosis: A Patient’s Perceptions of Over-the-Counter Medications and Their Adverse Effects - Mark D. Salter (Case Reports in Critical Care)
We highlight a case of distal renal tubular acidosis secondary to ibuprofen and codeine use. Of particular interest in this case are the patient’s perception of over-the-counter (OTC) medication use, her own OTC use prior to admission, and her knowledge of adverse reactions or side effects of these medications prior to taking them.